An investigation of strain differences in Pomphorhynchus laevis (acanthocephala) : an ecological, morphological and molecular approach - O'Mahony, Ellen Maria (Trinity College (Dublin, Ireland). Department of Zoology, 2003)
Kennedy, Bates and Brown (1989) stated that in the British Isles the acanthocephalan, Pomphorhynchus laevis could be separated into three strains, an English, Irish and marine strain. Much ecological evidence exists in support of this hypothesis. The three strains use different hosts to complete their life cycles (Hine and Kennedy, 1974a; Kennedy, 1984; Molloy, Holland and O’Regan, 1995), they are located in different sections of the definitive host’s gut (Broughton, Hine and Kennedy, 1976; Fitzgerald and Mulcahy, 1983; Kennedy, 1984) and geographically they are largely confined to different areas, though the marine and English freshwater strains do overlap in certain river estuaries (Hine and Kennedy, 1974a; Kennedy, 1984; Guillen-Hemandez and Whitfield, 2001). In the thesis presented here, ecological and other evidence will be presented in support of the strain hypothesis. Four samples of brown trout were collected per year over a two-year period from L. Feeagh, Co. Mayo. This enabled a detailed study of the ecology of the Irish strain. Differences between the Irish and other strains, which were highlighted in previous studies, were confirmed (Fitzgerald and Mulcahy, 1983; Molloy et al, 1995). One of the most striking differences between the Irish strain and others is its seasonal pattern of growth and maturation. This may be due to the limited breeding potential of the intermediate host, compared to similar animals in Britain, which affects the transmission dynamics of the parasite (Fitzgerald, 1987). It may also be due to low temperatures preventing growth of the parasite over the winter period (Brown, 1989).
Keywords: Zoology, Ph.D.; Ph.D. Trinity College Dublin